Risk Factors for Cardiovascular Diseases among Young Office Workers (Medical Forum Monthly, 2024)
Objective: To determine the frequency of risk factors associated with development of cardiovascular disease amongst young office workers.Study Design: Descriptive / cross-sectional study.Place and Duration of Study: This study was conducted at the Medical Outdoor Department of Services Hospital Lahore from 1st January 2017 to 31st July 2017.Materials and Methods: A total of 150 office workers aged 25-35 years and either gender were included. Those employees that did not complete the proforma were excluded from the final analysis. The demographic details of family history, past history regarding diabetes, hypertension, hypercholesterolemia and MI were recorded. Other risk factors that were investigated included physical inactivity, smoking and occupational stress were also recorded.Results: There 120 males and 30 females with mean age of the patients was 31.2±3.9 years. .Occupational stress was identified as the most important risk factor found in upto 80% of the employees. Other common risk factors included smoking prevalent in 45.8% of workers and lack of physical activity reported by 40% of the employees. Diabetes was prevalent in only 6.7% of the workers.Conclusion: Occupational stress, physical inactivity and smoking are the common risk factors prevalent among young employees. These potentially modifiable risk factors need to be controlled in order to reduce the incidence of cardiovascular disease.